How do I find the inverse of this equation
in Calculus Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

Let y=(x³-4)/(x³-3), y(x³-3)=x³-4, yx³-3y=x³-4, yx³-x³=3y-4, x³=(3y-4)/(y-1), x=∛((3y-4)/(y-1))=f⁻¹(y).

f⁻¹(x)=∛((3x-4)/(x-1)).

by Top Rated User (645k points)

Related questions

2 answers
1 answer
asked Jul 15, 2017 in Other Math Topics by anonymous | 76 views
0 answers
2 answers
asked May 10, 2013 in Algebra 2 Answers by anonymous | 147 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
82,917 questions
87,575 answers
1,965 comments
4,217 users